2021
DOI: 10.1177/17588359211042224
|View full text |Cite
|
Sign up to set email alerts
|

Specialist palliative and end-of-life care for patients with cancer and SARS-CoV-2 infection: a European perspective

Abstract: Background: Specialist palliative care team (SPCT) involvement has been shown to improve symptom control and end-of-life care for patients with cancer, but little is known as to how these have been impacted by the COVID-19 pandemic. Here, we report SPCT involvement during the first wave of the pandemic and compare outcomes for patients with cancer who received and did not receive SPCT input from multiple European cancer centres. Methods: From the OnCovid repository ( N = 1318), we analysed cancer patients aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(60 reference statements)
1
4
0
Order By: Relevance
“…Furthermore, because of the unpredictable course of COVID-19, it might have been difficult to assess which patients would not benefit from further hospital care. A previous study has also shown that lack of consultation of SPC in hospitals decreased the number of patients referred to EOL care in patients with COVID-19 and cancer, 19 and in our study, only 14% of patients received palliative consultation, which might have decreased referral to SPC.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…Furthermore, because of the unpredictable course of COVID-19, it might have been difficult to assess which patients would not benefit from further hospital care. A previous study has also shown that lack of consultation of SPC in hospitals decreased the number of patients referred to EOL care in patients with COVID-19 and cancer, 19 and in our study, only 14% of patients received palliative consultation, which might have decreased referral to SPC.…”
Section: Discussionsupporting
confidence: 46%
“…Breathlessness was a common symptom in this study, which is in accordance with other studies among patients with COVID-19 6 , 10 and also among patients with COVID-19 and cancer during EOL. 19 More patients within the hospital group suffered from breathlessness, which indicates that they might have had more severe lung complications from COVID-19. A lower symptom burden during EOL among nursing-home residents with a COVID-19 infection compared to elderly patients in hospitals has previously been shown, which also is an indication that those with more severe COVID-19 have an increased probability of being hospitalized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following on the patient's readiness and autonomy, the palliative cancer patient care will be moved from the hospital to the community, as chosen by the patients. SPC has shown the impacts on improving the patient quality of life, reducing the stress of the patient and family, lowering the aggressive medical treatment and hence the hospital costs, and even on increasing patient life expectancy (32) The United Kingdom (UK) serves as a successful example of the well-developed Specialist Palliative Care (SPC) system that has signi cantly improved access to high-quality palliative care services. By 2005, the UK had established 361 hospitals offering SPC, along with 277 community palliative care nurses.…”
Section: Discussionmentioning
confidence: 99%